Influence Of Demographic Factors And History Of Malaria With The Incidence Malaria In MORU PHC - Sudirman Manumpa (Jurnal Berkala Epidemiologi, 2016)
Malaria morbidity in the 2014 Public health center (PHC) of Moru with Annual Parasite Incident (API) parameter of 16.9%. This figure is still high compared to the malaria elimination target in Indonesia in 2030, which is <1%. The incidence of malaria is more common in children younger than 12 years. The high number of malaria causes poverty, low levels of learning achievement of children, and in pregnant women causes low birth weight in infants and death. The purpose of this study was to analyze the factors that influence the incidence of malaria in the work area of PHC of Moru, Alor Barat Daya District, Alor Regency. This study uses a cross-sectional design. The study population was all patients who had peripheral blood tests at the PHC of Moru laboratory unit from June to October 2015. The number of samples in this study was 173 respondents. The sampling technique is simple random sampling. Data collection instruments are questionnaires and observation sheets. The results of the study with the Chi-Square test found that the factors that influence the incidence of malaria were socioeconomic status (p = 0,000) and level of education (p = 0.001). The results of the logistic regression test found that ages 25–76 years (p = 0.025) and socioeconomic status (p = 0,000) were factors that influenced the incidence of malaria. Variables that influence malaria incidence from causal factors are demographic factors such as age, education level, socioeconomic status. So it is suggested that the socialization of malaria occurrences in community groups with elementary school education level. Community economic empowerment by utilizing dams for agriculture and lagoon for aquaculture. Evaluation of malaria incidence and follow-up of treatment management for malaria management will be more appropriate and targeted.